التغير الدلالي في معجم لسان العرب باب الباء أنموذجا - عوادي, زلومة, أيوب أسماء; زايدة, مروة (Univercty of Eloued, 2020)
يتناول هذا البحث موضوع التغير الدلالي بين الدرس الدلالي والدرس المعجمي، حيث لابد لباحث اللغة أن يلم ببعض جوانبه لما له من أهمية في بيان حياة اللغة ودلالتها عبر الأزمان ، حيث يلاحظ التغيارت التي طأرت على اللفظة وذلك عبر مارحل زمانية متفاوتة تكون الألفاظ ، فقد تتسع لتشمل عدد أكبر من المعاني وقد تضيق لتقتصر على معنى بعين ه ،في حركة دائبة فلطالما كان موضوع التغير الدلالي موضع اهتمام لدى ، وقد تنتقل من مجال الى مجال آخر الدارسين. واقتضى منا موضوع البحث اتباع المنهج الوصفي ، الذي يارفق حياة اللفظة والتغير الحاصل الذي يطأر عليها، اضافة الى المنهج التاريخي، الذي يارفق دارسة حياة اللفظة وكيفية عرضها على معجم لسان العرب This research deals with the theme of Semantic change between Semantic lesson and Lexical lesson where the language researcher must accustom some aspects of it because of its importance in the Statement of pronouncement and its Significance through time Anyone can notice the changes that have been changed on words across varying time stages where in perpetual movement The pronunciation expanded to include greater number of meaning itself and it may move from one domain to another as long as the topic(subject) of the Semantic change is important for many scholars. The topic of the research is required to follow the descriptive method which accompanied the word's life and the changes that many occur on it ،in addition to the historical curriculum which accompanied the Study of the word's life and how
Keywords: الدلالة، علم الدلالة، التغير، التغير الدلالي، المعجم.; Semantics ، indication ،the change ،Semantic change ،Lexicone